Respuesta :

Answer:

See Below

Step-by-step explanation:

That rule is a transformation across the x-axys.

Assigne a letter to each point:

A = (2, 7) => A' = (2, -7)

B = (-5, -2) => B' = (-5, 2)

C = (4, -3) => C' = (4, 3)

Ver imagen luchoprat

Answer:

The required graph of the image is shown below

Step-by-step explanation:

Consider the provided figure.

The coordinates for the given triangle are:

(2,7), (4,-3) and (-5,-2)

Now we need to transformation that has the rule (x, y) 》(x, -y)

So change the sign of y coordinate by using the above rule:

(2,-7), (4,3) and (-5,2)

Now plot the points and join them.

The required graph of the image is shown below

Ver imagen FelisFelis
ACCESS MORE